Factors influencing the implementation of Epilepsy Specialist Nurse role: Using the Consolidation Framework for Implementation Research. Issue 7 (5th February 2020) - Higgins, Agnes; Murphy, Rebecca; Downes, Carmel; Varley, Jarlath; Begley, Cecily; Elliott, Naomi
Abstract: Background: Research to support the added value of including Epilepsy Specialist Nurses as members of the multidisciplinary team is developing, yet little information exists on factors influencing the translation of these roles into practice. Aim: To describe the enabling and inhibiting factors to the implementation of the Epilepsy Specialist Nurse role in the Republic of Ireland. Methods: A qualitative design involving semi‐structure interviews, observation and analysis of documents, such as portfolios was used. The sample included 12 Epilepsy Specialist Nurses, 24 multidisciplinary team members, and 35 individuals with epilepsy and family members. Data were analysed using the Consolidation Framework for Implementation Research. Reporting rigour is demonstrated using the COREQ checklist (See Appendix S1). Results: While there was overwhelming support for the role, barriers and enablers were identified across all domains of the Consolidation Framework for Implementation Research. Enablers included national policies and guidelines, leadership from senior nursing and medical colleagues, climate of learning and mentorship, networking opportunities, infrastructural supports and competence of Epilepsy Specialist Nurses. Barriers included the limited consideration of service expansion and the increasingly complex nature of clinical cases on workload capacity. Deficits in infrastructural supports, challenges in relation to role preparation, role implementation and role responsibility, including concerns around lone practitioner models and concerns that the role was a cost‐saving measure, also emerged as potential barriers to future sustainability. Conclusion: The Consolidation Framework for Implementation Research offers researchers a pragmatic typology for analysing interrelationships between enabling and inhibiting factors that impact implementation of advanced practice roles, across different evidence sources, disciplines and boundaries. Relevance to clinical practice: In order to secure role sustainability, managers need to address the rate of service expansion, models of role development, deficits in supports and perceived motivations for role development on the quality, acceptability and sustainability of services provided.